Efficacy and Safety of Nitazoxanide, Albendazole, and Nitazoxanide-Albendazole against Trichuris trichiura Infection: A Randomized Controlled Trial - Speich, Benjamin (Public Library of Science, 2012)
BACKGROUND: The currently used anthelmintic drugs, in single oral application, have low efficacy against Trichuris trichiura infection, and hence novel anthelmintic drugs are needed. Nitazoxanide has been suggested as potential drug candidate. METHODOLOGY: The efficacy and safety of a single oral dose of nitazoxanide (1,000 mg), or albendazole (400 mg), and a nitazoxanide-albendazole combination (1,000 mg–400 mg), with each drug administered separately on two consecutive days, were assessed in a double-blind, randomized, placebo-controlled trial in two schools on Pemba, Tanzania. Cure and egg reduction rates were calculated by per-protocol analysis and by available case analysis. Adverse events were assessed and graded before treatment and four times after treatment. PRINCIPAL FINDINGS: Complete data for the per-protocol analysis were available from 533 T. trichiura-positive children. Cure rates against T. trichiura were low regardless of the treatment (nitazoxanide-albendazole, 16.0%; albendazole, 14.5%; and nitazoxanide, 6.6%). Egg reduction rates were 54.9% for the nitazoxanide-albendazole combination, 45.6% for single albendazole, and 13.4% for single nitazoxanide. Similar cure and egg reduction rates were calculated using the available case analysis. Children receiving nitazoxanide had significantly more adverse events compared to placebo recipients. Most of the adverse events were mild and had resolved within 24 hours posttreatment. CONCLUSIONS/SIGNIFICANCE: Nitazoxanide shows no effect on T. trichiura infection. The low efficacy of albendazole against T. trichiura in the current setting characterized by high anthelmintic drug pressure is confirmed. There is a pressing need to develop new anthelmintics against trichuriasis. TRIAL REGISTRATION: Controlled-Trials.com ISRCTN08336605